2014
DOI: 10.1097/mcp.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders in adults with epilepsy

Abstract: Identifying and treating unrecognized sleep disorders and understanding the impact of circadian rhythms on epilepsy can improve quality of life and seizure control in AWE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…This is in accordance with the few data in the literature reporting frequencies of insomnia similar to ours 4,11,19. After all, it is well known that there are several factors which can cause insomnia in patients with epilepsy: sleep fragmentation due to recurrent seizures, the effect of some AEDs, as well as the simultaneous presence of mood disorders.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with the few data in the literature reporting frequencies of insomnia similar to ours 4,11,19. After all, it is well known that there are several factors which can cause insomnia in patients with epilepsy: sleep fragmentation due to recurrent seizures, the effect of some AEDs, as well as the simultaneous presence of mood disorders.…”
Section: Discussionsupporting
confidence: 93%
“…Insomnia is usually present in 30–40% of patients. While the frequency of OSAS ranges from 10% to 30%, and that of RLS from 10% to 33%4,10,11 It is possible that the alterations between the different studies investigating sleep disorders in patients with epilepsy are partially related to biases in the selection of patients, but also to the use of different tests, different sample sizes as well as to differences in the type of treatment (mono-poly-therapy) 12. In fact, many studies have focused their attention only on a population of patients with focal epilepsy undertaking a multidrug treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In an excellent atlas, the Gibbses ( 1 ) described the NREM sleep enhancement of interictal epileptic discharges (IEDs). Several authors ( 2 4 ) summarized the related data, mainly on the distribution of spikes and seizures across sleep stages in different epilepsies. The growing knowledge about sleep physiology in the end of the last century increased the interest in sleep grapho-elements and their role in epilepsies.…”
Section: Introductionmentioning
confidence: 99%
“…Often, these disruptions manifest in the form of increased latency to sleep or premature waking, suggesting that dysfunction of the circadian clock may underlie some sleep issues. Conversely, disruptions in sleep are known to alter neurological symptoms, including those common to MEs such as seizure frequency and cognitive ability, and metabolic function in diseases such as type II diabetes (Suzuki et al, 1997, Grigg-Damberger and Ralls, 2014, Jain and Kothare, 2015, Nedeltcheva and Scheer, 2014, Guarnieri and Sorbi, 2015). Additionally, it has recently been shown that sleep deprivation alters mitochondrial function and gene expression in response to oxidative stress in Drosophila (Rodrigues et al, 2018).…”
Section: Introductionmentioning
confidence: 99%